The Limits of Resilience: Why Self-Efficacy Fails to Mitigate Technostress during Radical Core Banking Transformations - Siska Hardiyanti Putri; Laila Refiana Said; Meiske Claudia; Doni Stiadi; Anna Nur Faidah (Arkus, 2026)
The digitalization of the banking sector has shifted from a competitive advantage to a survival imperative. However, the migration to radical Core Banking Systems often precipitates Technostress, a phenomenon that threatens employee well-being. This study investigates the impact of Technostress on Work-Life Balance among banking professionals during a high-stakes digital transformation involving the implementation of the Temenos T24 system. Crucially, it challenges the prevailing assumption that individual Self-Efficacy serves as a universal buffer against these stressors. A quantitative, explanatory study was conducted on a purposive sample of 107 frontline and back-office staff at a Regional Development Bank in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0 to assess the measurement and structural models. The findings reveal that Technostress exerts a potent and significant negative effect on Work-Life Balance (path coefficient -0.29, p value 0.000). Paradoxically, and contrary to established theoretical expectations, Self-Efficacy failed to moderate this relationship (path coefficient 0.06, p value 0.500). In conclusion, the study identifies a Limit of Resilience, suggesting that during radical and structural technological upheavals, individual psychological resources such as Self-Efficacy are overwhelmed by systemic techno-overload and invasion. This shifts the onus of intervention from individual coping strategies to organizational job redesign.